INCLUSIVE EDUCATION AND EDUCATIONAL OPPORTUNITIES FOR PERSONS WITH DISABILITIES - Mamajonova Zebiniso Baxtiyor qizi (PEDAGOGS, 2025)
Abstract: This article explores the educational opportunities for persons with disabilities and the concept of inclusive education. It analyzes the key principles, necessary conditions, and the role of inclusivity in social development. The discussion highlights the importance of physical infrastructure, teacher training, didactic resources, and social support. By examining international experiences and recent reforms in Uzbekistan, the article demonstrates the positive outcomes of inclusive education. It concludes that guaranteeing equal educational rights for all children strengthens tolerance, solidarity, and social cohesion within society.